Um jogo de sedução e persuasão: figuras de retórica nas imagens veiculadas nos jingles das campanhas presidenciais de Dilma e Aécio em 2014 - Vidal, Luanny Maria Almeida (2016)
Political campaigns use various argumentative techniques in order to construct an efficient discourse that is able to touch the audience’s emotions. Thus, in the political discourse, voters usually come across election advertising that use figures of rhetoric applied as argumentative techniques. This paper aims to identify the figures of rhetoric present in two jingles broadcast in election propaganda on TV during the Brazilian presidential elections of 2014. This way, it intends to understand the role of figures of rhetoric in these discourses in order to verify the way they reinforce the orator's image (ethos). We also intend to understand how they contribute to the intensification of the arguments (logos), and in what ways they arouse passions (pathos) in the audience. As a theoretical basis, we selected some works of Rhetoric and Argumentation, such as the works of Aristotle (2003), Reboul (2004), Meyer (2007), Perelman & Olbrechts-Tyteca (2014), Fiorin (2014; 2015) and Ferreira (2015). This proposed research takes as its object of investigation verbal-visual texts, more specifically, the jingles broadcast on TV. The corpus comprises two jingles, which started Dilma Rousseff's (PT) and Aécio Neves’ (PSDB) political campaigns. The qualitative and comparative analysis showed that the figures contribute significantly to the process of persuasion once they touch the audience emotionally. This academic investigation seeks to contribute for the comprehension of the presence and argumentative effects of the use of figures of speech in political campaigns.